Association between nutritional status, frailty domains, physical activity, physical fitness, emotional status and quality of life with sarcopenia among older adults in Kelantan - Ganggaya, Keerthana Sree (2024)
Sarcopenia is a disease that affects health, functional independence and the quality of life among older adults which leads to adverse effects like falls, physical disability, hospitalization and mortality. Therefore, the current study aimed to assess the association between frailty domains, nutritional status, physical fitness, physical activity, emotional status, cognitive function and well-being of older adults with sarcopenia. This crosssectional study involved 287 community-dwelling older adults in Kelantan aged 60 and above, recruited through simple random sampling. The data collected were entered and analyzed using IBM SPSS Statistics 26 software. Data on socio-demography, sleep quality, supplement intake, geriatric syndrome, medical history, self-rated health status, frailty domains, cognitive function, functional limitation, physical activity, anthropometry, body composition, blood pressure, handgrip strength, physical fitness, emotional status, quality of life and sarcopenia were obtained through interview administered method. Binary logistic regression analysis was used to determine the factors associated with sarcopenia. The prevalence of possible sarcopenia, sarcopenia and severe sarcopenia were 59%, 9% and 14% respectively which was higher in men than in women (p = 0.029). A total of 84.0% of sarcopenic subjects were underweight while 46.7% of possible sarcopenia subjects were overweight which could lead to sarcopenic obesity. Significant association was found between physical frailty and sarcopenia (p <0.001) but not social frailty (p = 0.227) and cognitive frailty (p = 0.345). Significant association was found between sarcopenia and poor nutritional status, lack of physical fitness and cognitive function. However, no significant association was found between sarcopenia, emotional status and quality of life among older adults in Kelantan. After adjusting for confounding factors such as age, gender, smoking and education years, the factors associated with sarcopenia were muscle mass, gait speed, sit-to-stand test and physical frailty were found to be factors associated with sarcopenia. Approximately, more than half of the community-dwelling older adults in this study had possible sarcopenia (59 %). Therefore, older adults should be educated on the steps to prevent sarcopenia via healthy eating, exercising, emotional stress management and involvement in voluntary activities.